INVESTIGATING TEACHERS’ BARRIERS TO ICT (INFORMATION COMMUNICATION TECHNOLOGY0 INTEGRATION IN TEACHING ENGLISH AT SENIOR HIGH SCHOOLS IN PEKANBARU - Sitti Hadijah; Shalawati Shalawati (Proceedings of ISELT FBS Universitas Negeri Padang, 2017)
As numerous issues of effective use of ICT (Information and Communication Technology) in English teaching and learning contexts, many teachers worldwide have been starting to deploy either simple of advanced technology products. However, some challenges are still inevitable, which affect the effectiveness of ICT integration in teaching and learning process. In this case, this paper reports an effort of investigating teachers’ barriers to ICT integration in teaching English at Senior High Schools in Pekanbaru. This study worked on descriptive research design in which qualitative and quantitative approaches employed to analyze the underlying barriers of ICT integration in English language teaching. Questionnaires were distributed to fourteen Senior High School teachers in Pekanbaru, and afterwards open-ended interview was also carried out to gather further information about the teachers’ barriers in integrating ICT. Then, the findings indicated that some barriers encountered by the teachers in term of accessibility of ICT, time, professional development, and technical support. Hence, these linking barriers suggest the teachers should be fully motivated and supported to engage with ICT in their teaching activities.